2021
DOI: 10.1038/s42003-021-01838-3
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of transient protein-protein interactions within carrier protein-dependent biosynthesis

Abstract: Fatty acid biosynthesis (FAB) is an essential and highly conserved metabolic pathway. In bacteria, this process is mediated by an elaborate network of protein•protein interactions (PPIs) involving a small, dynamic acyl carrier protein that interacts with dozens of other partner proteins (PPs). These PPIs have remained poorly characterized due to their dynamic and transient nature. Using a combination of solution-phase NMR spectroscopy and protein-protein docking simulations, we report a comprehensive residue-b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 67 publications
(87 reference statements)
4
23
0
Order By: Relevance
“…During the continuously maturation of the intermediate, ACP must form specific protein-protein interactions, and the tethered intermediate should be translocation from the hydrophobic core of ACP into the active site of the partners. The ACP-mediated assembly pattern in the natural product biosynthesis pathway offers a safe, efficient, and economical program to facilitate the direct production of the final compounds [22,30,32]. Combined with our present investigations, the AHBA-tethered MmcB triggered the biosynthesis of the early-stage of mitomycin C. In this reaction, MmcB specifically interacted with the partners, such as MitE, MitF, and others, to afford the mitosane skeleton.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…During the continuously maturation of the intermediate, ACP must form specific protein-protein interactions, and the tethered intermediate should be translocation from the hydrophobic core of ACP into the active site of the partners. The ACP-mediated assembly pattern in the natural product biosynthesis pathway offers a safe, efficient, and economical program to facilitate the direct production of the final compounds [22,30,32]. Combined with our present investigations, the AHBA-tethered MmcB triggered the biosynthesis of the early-stage of mitomycin C. In this reaction, MmcB specifically interacted with the partners, such as MitE, MitF, and others, to afford the mitosane skeleton.…”
Section: Discussionsupporting
confidence: 69%
“…Remarkably, the ACP-dependent tailoring enzymes are involving in the biosynthesis of a large number of important chemical molecules, from primary metabolites to structurally complex natural products [18,29,30]. The ACP is a relatively small protein with a dynamic and monomeric helical bundle architecture, which shuttles the nascent cargo to the partner enzymes for decoration through the biosynthetic machinery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting docking poses were organized based on RMSD from the previously published model of the C8-AcpP • LipB docked complex 20 (Figure S10). The methodology used was the same as we previously developed to model six ACP-partner protein interfaces from E. coli FAB and benchmark them with established crystal crosslinked structures 23 .…”
Section: Docking Analysis To Identify Chain Length Specific Interactionsmentioning
confidence: 99%
“…This data was then used to guide high-resolution in silico docking to identify the surface features responsible for the experimentally identified binding differences. We have shown that the implementation of NMR titration experiments to guide docking algorithms can accurately and reproducibly deduce PPI poses in ACP-dependent pathways 23 .…”
Section: Introductionmentioning
confidence: 99%